(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
According to an analysis of the main statistical indicators, in recent years there have been serious quantitative and qualitative changes in the structure of traumatic brain injury, consisting of an increase in the number of victims with severe, life-threatening injuries. When investigating crimes against human life and health, an important place belongs to forensic medical examination, without which it is impossible to establish the mechanism and duration of injury, the nature and severity of the damage.